2011
DOI: 10.1104/pp.111.175257
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Ca2+/H+ Transport Activity Is Required for Systemic Phosphate Homeostasis Involving Shoot-to-Root Signaling in Arabidopsis    

Abstract: Calcium ions (Ca 2+ ) and Ca 2+ -related proteins mediate a wide array of downstream processes involved in plant responses to abiotic stresses. In Arabidopsis (Arabidopsis thaliana), disruption of the vacuolar Ca 2+ /H + transporters CAX1 and CAX3 causes notable alterations in the shoot ionome, including phosphate (P i ) content. In this study, we showed that the cax1/cax3 double mutant displays an elevated P i level in shoots as a result of increased P i uptake in a miR399/PHO2-independent signaling pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 58 publications
0
51
0
Order By: Relevance
“…The P phenotype of this double mutant suggest that CAX transporters alter root–shoot signalling during phosphate starvation (Liu et al . 2011). Furthermore, transcriptomic microarray data of the double mutant further document what one would expect, a multitude of changes in gene expression (Conn et al .…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
“…The P phenotype of this double mutant suggest that CAX transporters alter root–shoot signalling during phosphate starvation (Liu et al . 2011). Furthermore, transcriptomic microarray data of the double mutant further document what one would expect, a multitude of changes in gene expression (Conn et al .…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
“…Because of the high amino acid sequence similarity among PHT1;1, PHT1;2, and PHT1;3, a common peptide was used to generate an antibody recognizing all three of them (Liu et al, 2011). The protein signals detected by immunoblot using these antibodies are specific because signals corresponding to the same size of protein in the T-DNA insertion mutants were not detected (phf1 and pht1;4) or reduced (pht1;1) compared with wild-type plants (see Supplemental Figures 3A and 3B online).…”
Section: Pho2 Negatively Regulates the Protein Abundance Of Phf1 And mentioning
confidence: 99%
“…The anti-PHT1;1 polyclonal rabbit antibody was raised and affinity purified against a peptide of PHT1;1 corresponding to the amino acid residues 266 to 285 (ELEERVEDDVKDPRQNYGLF) (Liu et al, 2011). The anti-PHT1;4 polyclonal rabbit antibody was raised and affinity purified against an internal fragment of PHT1;4 corresponding to the amino acid residues 265 to 283 (IEPEQQKLEEISKEKSKAF).…”
Section: Antibody Productionmentioning
confidence: 99%
“…Notably, a total of seven Pi starvation-induced genes were found in the top 10 list of SAP11 AYWB -elicited genes. Further comparison revealed that more than 20% of the SAP11 AYWB -elicited genes (P , 0.001) overlapped with the differentially expressed genes (more than 2-fold up-regulation) identified by Müller et al (2007) and Liu et al (2011) under Pi starvation conditions (Fig. 4B).…”
Section: Genome-wide Identification Of Differentially Expressed Mrnasmentioning
confidence: 99%
“…Taken together, these results indicate that Pi starvation-induced genes are highly up-regulated by the expression of SAP11 AYWB in Arabidopsis. Liu et al (2011) from leaf and root samples, respectively, in response to Pi starvation. C, The mRNA levels of differentially expressed genes identified in the 35S::SAP11 AYWB transgenic line number 13 were examined by qRT-PCR and normalized to Actin2.…”
Section: Genome-wide Identification Of Differentially Expressed Mrnasmentioning
confidence: 99%